2011
DOI: 10.1111/j.1476-5381.2011.01442.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting actions of diesel exhaust particles on the pulmonary and cardiovascular systems and the effects of thymoquinone

Abstract: BACKGROUND AND PURPOSEAcute exposure to particulate air pollution has been linked to acute cardiopulmonary events, but the underlying mechanisms are uncertain. EXPERIMENTAL APPROACHWe investigated the acute (at 4 and 18 h) effects of diesel exhaust particles (DEP) on cardiopulmonary parameters in mice and the protective effect of thymoquinone, a constituent of Nigella sativa. Mice were given, intratracheally, either saline (control) or DEP (30 mg·per mouse). KEY RESULTSAt 18 h (but not 4 h) after giving DEP, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 52 publications
5
109
2
3
Order By: Relevance
“…Pretreatment of mice with TQ prevented DEP-induced decrease of systolic blood pressure and leucocytosis, increased IL-6 concentration and decreased plasma SOD activity. TQ also prevented the decrease in platelet numbers and the prothrombotic events but not platelet aggregation in vitro [79] .…”
Section: Cardiovascular Activitymentioning
confidence: 97%
“…Pretreatment of mice with TQ prevented DEP-induced decrease of systolic blood pressure and leucocytosis, increased IL-6 concentration and decreased plasma SOD activity. TQ also prevented the decrease in platelet numbers and the prothrombotic events but not platelet aggregation in vitro [79] .…”
Section: Cardiovascular Activitymentioning
confidence: 97%
“…19,20 Briefly, the trachea was intubated after induction of anesthesia with urethane (1 mg/g body weight, IP), and a 2F venous catheter (Sims Portex Ltd., Hythe, Kent, UK) was inserted in the right jugular vein for the administration of fluorescein (Sigma-Aldrich Co., St Louis, MO, USA). After that, a craniotomy was first performed on the left side, using a microdrill, and the dura was stripped open.…”
Section: Experimental Pial Venular Thrombosis Modelmentioning
confidence: 99%
“…36 Previous reports showed that pulmonary exposure to pollutant particles and some engineered NPs induce systemic and cardiovascular events. 22,24,37,38 The latter effects were explained by the capacity of NPs to induce lung inflammation, which causes systemic inflammation and oxidative stress, and/or the aptitude of NPs to traverse the air-blood barrier to enter the blood and affect cardiovascular endpoints. 5,18 It has been reported that IV administration of CeO 2 NPs induce liver injury and oxidative stress.…”
mentioning
confidence: 99%
“…27,37,45 In this model, the damage to endothelial cells causes the platelets to adhere at the site of endothelial damage and then aggregate. 27,37,45 The data of the present study show that acute IT administration of CeO 2 NPs induced a significant and dose-dependent shortening of the thrombotic occlusion time in pial arterioles and venules, indicating that CeO 2 NPs possess prothrombotic effects. Along with thrombosis in vivo, a dose-dependent and significant increase in the concentrations of the coagulation factor, fibrinogen, and PAI-1 in the plasma following acute exposure to CeO 2 NPs was found.…”
mentioning
confidence: 99%
See 1 more Smart Citation